Person-centered care for dementia patients (back-end system development) - Ang, Edmund Yun Kiong (Nanyang Technological University, 2022)
Dementia is a syndrome that interferes with a person's daily life activities by causing the loss of the ability to think, remember, and reason. Currently, dementia is incurable, however there are treatments that can reduce the symptoms. At person-centered care centres, such non-pharmacological therapy is provided. They provide a person’s care by taking their history, abilities, personality, and interest into consideration. Although there is no effective pharmacological treatment currently available, research has shown that non-pharmacological treatments may be effective. Examples of non-pharmacological treatments that have shown to be effective are person-centred care and game-based intervention. In view of the effectiveness of these non-pharmacological treatments, Person-Centred Care (PEAR) management system was created, to assist care centre’s staff and healthcare professionals in providing better care for dementia patients and at the same time, reduce manpower required to manage centre activities. The objective of this project is to maintain and improve the PEAR’s backend system and web application which are passed down by the previous batch, as well as continue the migration from the old system to the new PEAR’s backend system, implement and improve on the Application Programming Interface (API) required by the frontend. Along the way, implement additional features that improve the overall experience of the web application.